Transatlantic intellectual networks in the General Studies university reform movement: the role of Puerto Rico. - Jorge, Rodríguez Beruff (Revista Educación Superior y Sociedad (ESS), 2019)
Although the General Studies movement had its beginnings in the United States in the 1920s, it developed important intellectual and institutional linkages with other related movements in Europe, the Caribbean, Central America and Latin America. Puerto Rico became part of that movement in the 1940s on the initiative of Chancellor Jaime Benítez and his collaborators. The influence of José Ortega y Gasset´s ideas on university reform in Puerto Rico predate the linking up with the General Studies movement in the United States. To a great extent, the links the University of Puerto Rico developed with both networks, the General Studies movement in the US and Ortega´s own political and philosophic networks in Spain and Latin America, were an important aspect both of its own reform process and the international prominence it gained during this period. The academic relationship with Costa Rica was particularly close. Puerto Rico’s role in these movements offers new insights into the mid 20th century university reform process by placing it in a broad international scenario.